JUDUL PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP TINGKAT KECEMASAN PADA PASIEN PRE OPERASI BEDAH MAYOR : LITERATURE REVIEW - dewi pujiana (IKesT Muhammadiyah Palembang, 2021)
THE EFFECTIVENESS OF THERAPEUTIC COMMUNICATION ON ANXIETY AMONG PATIENTS WITH PRE –MAJOR SURGERY : LITERATURE REVIEW Abstract Background: Patients often experience anxiety with various risks or bad possibilities that can occur in undergoing surgery, especially major surgery. One of the efforts in dealing with anxiety is through trerapeutic communication during preoperative major sirgery. Therapeutic communication can increase patient confidence in facing an operation. Study Purpose : Writing this literature Review aimed to determine the effect of nurse therapeutic communication on anxiety levels in patients with pre-major surgery. Methods: This study, used the Literature Review method by taking data sources using electronic databases such as PubMed, National Library and Google Schloar to answer the purpose of writing. Articles published in the period 2016-2020 which selection and identification according to the inclusion criteria, There are 10 articles that will be reviewed. Results: Based on the results of the review of the 10 research articles, it was explained that there was a significant effect after nurse therapeutic communication was carried out on the level of anxiety in patients with pre-major surgery, such as decreasing anxiety in patients with pre-major surgery. Conclusion: Therapeutic communication is very effective in reducing anxiety levels on patient pre-major surgery, so that it can be applied in nursing care for patients who will undergo the surgery process Keywords : Therapeutic Communication, Anxiety, Pre-Major Surgery.